Optimasi Injeksi Trisodium Phosphate Pada Air Suplai Boiler Di Unit 4 PLTU Nagan Raya Menggunakan Design Expert Metode Pendekatan Response Surface Bok-Behnken - Lubis, Fadhil Ramadhan (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
In the steam power plant industry, supporting facilities commonly called BOP (Balance of Plant) include Coal Handling, Ash Handling and WTP (Water Treatment Plant). TSP Trisodium Phosphate is one of the chemicals in water treatment. Besides functioning as a cleaner, TSP also functions to precipitate magnesium, iron, and silica and is able to help maintain the pH value of boiler water. Therefore, this activity was carried out to optimise chemical injection in the water treatment process for boiler water with good quality so as to produce steam with good quality as well. From the analysis results, the optimum injection of chemicals is 0.462 ppm TSP (Trisodium Phosphate) resulting in a pH value of 9.279, SiO2 (Sillicon dioxyde) 64.5 ppb, and Na+ (Sodium) 0.719 ppb.